Comparing the hearing threshold between posterior auricular muscle response (pamr) and pure tone audiometry (PTA) in impaired hearing individuals - Abdul Manan, Aifaa (2015)

(untitled)
The aim of this study is to estimate and to compare the mean hearing thresholds in cochlear hearing loss and CHL using PAMR and PTA. Then, the hearing thresholds of PAMR and PTA in cochlear hearing loss and CHL patient are compared in order to determine the correction factors. METHOD This is a cross sectional study conducted at Audiology Clinic, Hospital USM starting from 1st June 2013 until 31st May 2014. It comprised of 76 volunteered subjects and aged ranging between 18 to 60 years. All patients were examined using otoscopy, tympanometry and then PTA. Tone decay test was done for patient with sensorineural hearing loss to exclude retrocochlear hearing loss. Subject with normal tone decay test will proceed with PAMR. Finally, the PAMR were performed by placing the positive electrode at the ear lobule, negative electrode at the posterior auricular muscle while the reference electrode was placed at the forehead. This PAMR were measured at frequencies 500, 1000, 2000 and 4000 Hz using tone burst stimuli and the subject was asked to make 70⁰ lateral eye turned to side of stimulus when the stimulus was being presented and the waves recorded. RESULT The PAMR thresholds noted were higher compared to the PTA thresholds. As there were differences in hearing thresholds between PAMR and PTA, the correction factors were determined. The correction factors decreased with increased in frequencies. In cochlear hearing loss patients, the correction factors were 26.29, 19.00, 16.00, 13.00 for 500, 1000, 2000 and 4000 Hz respectively. In CHL patients, the correction factors were 20.29, 18.68, 14.12, 12.06 for 500, 1000, 2000 and 4000 Hz respectively. CONCLUSION PAMR can be used as one of objective tests to determine hearing thresholds since all the subjects had recordable PAMR waves with eye turned position. However, because of difference in PAMR thresholds compared to PTA, the correction factors should be applied to PAMR threshold in order to estimate PTA thresholds.